The Role of Perceived Fit, Attitude, and Need for Uniqueness on Intention to Purchase Co-Branded Product in Indonesia - Romeyna Willim; Keni Keni; Ai Ping Teoh (International Journal of Application on Economics and Business, 2023)
This research was conducted to empirically examine the role of perceived fit, attitude, and need for uniqueness to increase intention to purchase co-branded product in Jakarta. A total of 202 respondents were collected with non-probability convenience sampling technique, but only 150 data were usable as samples. An online questionnaire was distributed using Google Form with 5-point Likert scale for each indicator. All data were analyzed using PLS-SEM method. The results showed that perceived fit does not positively and significantly impact intention to purchase co-branded product. In addition, attitude and need for uniqueness can positively and significantly impact intention to purchase co-branded product. The results of this study contribute to get a better understanding of co-branding and to help the marketers formulate better co-branding strategies.